O vplivu oberammergauskih pasijonskih iger na Pasijon Ksaverja Meška - Drnovšek, Jaša (Bogoslovni vestnik, 2023)
The author examines how the Oberammergau Passion Play, which the Slovenian writer Ksaver Meško (1874–1964) attended in 1910, influenced his 1936 drama The Passion Play. In the first part of the paper, the author introduces the genre of the Passion play, places Meško’s Passion Play in his literary oeuvre, explains the broader cultural-historical background of its creation, and presents the centuries-old tradition of the Oberammergau Passion Play. In the second part of the paper, the author analyses and compares Meško’s Passion Play with the so-called official text of the Oberammergau Passion Play, which was published especially for the performances in 1910. The author identifies possible influences that manifest themselves throughout Meško’s text both on a formal level and on a content level: in the prologue, in the prefiguration scenes, in the central plot and also at the end of his Passion Play.
Keywords: amateur theatre; ljubiteljsko gledališče; Meško, Franc Ksaver; Oberammergau; Oberammergau Passion Play; oberammergauske pasijonske igre; pasijonska igra; Passion Play